The reimbursement decision speed for oncology new drugs in China and its determinant factors - Xingyue Zhu; Yang Chen (Frontiers in Public Health, 2023)
IntroductionChina has initiated national price negotiations to improve access to innovative drugs. Learning the factors that contributed to the time gap from marketing authorization to reimbursement leads to more clarity to decision-making, which remains under-researched in China.MethodsWe collected new oncology drug approvals that were marketed before 30 Jun 2022, using the Listed Drug Database of the Chinese drug agency. Major information of each approval was obtained from the published review report, including the first approval region (China or the US) and the receipt of expedited review pathways (priority review and conditional approval). The reimbursement lists issued by China National Healthcare Security Administration from 2015 to 2023 were used to determine the reimbursement status of drugs. The duration from marketing authorization to reimbursement was defined as the reimbursement decision speed, and the Cox regression was performed to explore the underlying factors.ResultsA total of 186 oncology approvals were included. More than half of the approvals qualified for reimbursement (110[59.14%]), and the median reimbursement decision speed was accelerated from 540.5 days in the third-round negotiation to 448 days in the seventh-round. Domestic new drugs had a higher probability of being adopted by the Chinese payer than drugs developed by foreign companies (adjusted HR = 3.73, 95% CI 2.42 to 5.75; P < 0.001). Furthermore, new drug applications receiving the regular review pathway were more likely to be reimbursed (adjusted HR = 2.15, 95% CI 1.13 to 4.08; P = 0.020) compared to those approved under the conditional approval pathway.DiscussionThese findings indicate that the Chinese government is actively working toward improving access to new oncology drugs. The faster reimbursement decision speed for domestic drugs might be attributed to their pricing advantages and the regulator's efforts to stimulate innovation in the domestic pharmaceutical industry. However, concerns about the uncertainty in drug benefits can affect the reimbursement decision-making, which suggests the delicate tradeoff between drug accessibility and risk involved in the reimbursement process.